Facile synthesis and self-cleaning application of bimetallic (CuSn, CuNi) dendrites - Biswas, Anupam; Kulkarni, Mayuresh A.; Bakthavatsalam, Rangarajan; Mondal, Sourik K.; Dwivedi, Pravin K.; Shelke, Manjusha V.; Devi, Radhamonyamma N.; Banpurkar, Arun G.; Kundu, Janardan (Chemistryselect, 2017)
Bimetallic dendrites (Au, Ag, Pt, Pd) have received intense research interest due to their applications in catalysis and sensing. However, reports on rational synthesis of non-noble bimetallic dendrites that finds self-cleaning applications are scanty. Here, we demonstrate one step co-reduction based galvanic replacement reaction (GRR) for synthesis of alloyed bimetallic dendrites (CuSn, CuNi) with controlled surface roughness and chemical composition. Probing their growth process reveals that i) for CuSn dendrites, co-reduction of Cu2+ and Sn2+ is observed throughout GRR; ii) for CuNi dendrites, Cu nanoparticle, that deposits initially, augments the reduction of Ni2+ which leads to CuNi alloy phase formation during later stages of GRR. These dendrites, naturally having dual degree of surface roughness (micro/nano), have been exploited here for fabricating superhydrophobic surfaces (SHS) with excellent self-cleaning abilities. They show enabling properties such as high contact angle, minimal contact angle hysteresis, and excellent Cassie state stability with no impalement. They maintain superhydrophobicity when exposed to different environmental conditions (low temperature, high temperature, exposure to corroding solutions and UV radiation). The present facile methodology for fabrication of bimetallic dendrites is beneficial for low-cost production of functional nano/micro-materials.

Biomass-mediated synthesis of Cu-doped TiO2 nanoparticles for improved-performance lithium-ion batteries - Kashale, Anil A.; Dwivedi, Pravin K.; Sathe, Bhaskar R.; Shelke, Manjusha V.; Chang, Jia-Yaw; Ghule, Anil V. (ACS Omega, 2018)
Pure TiO2 and Cu-doped TiO2 nanoparticles are synthesized by the biomediated green approach using the Bengal gram bean extract. The extract containing biomolecules acts as capping agent, which helps to control the size of nanoparticles and inhibit the agglomeration of particles. Copper is doped in TiO2 to enhance the electronic conductivity of TiO2 and its electrochemical performance. The Cu-doped TiO2 nanoparticle-based anode shows high specific capacitance, good cycling stability, and rate capability performance for its envisaged application in lithium-ion battery. Among pure TiO2, 3% Cu-doped TiO2, and 7% Cu-doped TiO2 anode, the latter shows the highest capacity of 250 mAh g(-1) (97.6% capacity retention) after 100 cycles and more than 99% of coulombic efficiency at 0.5 A g(-1) current density. The improved electrochemical performance in the 7% Cu-doped TiO2 is attributed to the synergetic effect between copper and titania. The results reveal that Cu-doped TiO2 nanoparticles might be contributing to the enhanced electronic conductivity, providing an efficient pathway for fast electron transfer.

Agro-waste extracted cellulose supported silver phosphate nanostructures as a green photocatalyst for improved photodegradation of RhB dye and industrial fertilizer effluents - Dwivedi, Pravin K.; Nair, Aathira; Mehare, Rupali S.; Chaturvedi, Vikash; Joshi, Kavita; Shelke, V. Manjusha (Nanoscale Advances, 2020)
The efficiency and reusability of photocatalysts are the dominant factors for their pragmatic use. The visible light induced semiconductor silver phosphate is a superior photocatalyst effective under visible light but its stability is still an undiscussed issue. To overcome this stability issue in this present manuscript, eco-friendly agro-waste extracted cellulose supported silver phosphate nanostructures have been designed for the first time through a simple chemical process. At first, silver phosphate nanostructures were synthesized by the co-precipitation method. Then, different weights of cellulose were added to the silver nitrate solution to form cellulose supported silver phosphate nanostructures. The photodegradation efficiency for each weight ratio was examined in which the photocatalyst Ag-8 nanostructures showed a high rate (0.024 min(-1)) for degradation of Rhodamine B (RhB) using a low intensity tungsten bulb. Real sample analysis has also been carried out using this photocatalyst for the degradation of industrial fertilizer effluents. The degradation rate of all the nanostructures was found to be high in comparison to pristine silver phosphate as well as the extracted bare cellulose. The photocatalytic activity is enhanced because of the participation of cellulose as a support which makes an interface for silver phosphate and assists it in delaying the charge recombination period under visible light. To understand the photochemical reaction of electrons and holes, scavenger studies were also performed.

Electrochemical performance of pre-lithiated ZnMoO4 and r-GO@ZnMoO4 composite anode for lithium-ion battery application - Bin Masood, Khalid; Parte, Golu; Jain, Neha; Dwivedi, Pravin K.; Kumar, Pushpendra; Shelke, V, Manjusha; Patel, Rp; Singh, Jai (Journal of the Taiwan Institute of Chemical Engineers, 2020)
Exploring a safer replacement of Li metal anode is crucial for technological, and fundamental importance. Li-metal is a preferred choice as anode material for lithium-ion battery (LIB) applications. However, parasitic dendritic growth on the Li metal surface during cycling causes instability and safety dreads. In the present study, we have investigated that the pre-lithiated ZnMoO4 is superior to its carbon-based counterparts (r-GO@ZnMoO4), moreover safer and sustainable than Li metal anode. The pre-lithiated ZnMoO4 delivers a better reversible capacity (similar to 1000 mAhg(-1) at 0.1 Ag-1), superior rate capability (similar to 400 mAh g(-1) at 2 Ag-1), and excellent cycling stability over 300 cycles at 0.1 Ag-1, as compared to bare ZnMoO4 and r-GO@ZnMoO4 composite. The present investigation is an attempt to provide a substitute for commonly used Li-metal/carbon anodes with better performance. (C) 2020 Taiwan Institute of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Cycling stability; Electrochemistry; Li-ion battery; Nyquist plot; Rate performance; ZnMoO4 nanocomposites

Experimental and theoretical investigations of the effect of heteroatom-doped carbon microsphere supports on the stability and storage capacity of nano-Co3O4 conversion anodes for application in lithium-ion batteries - Dwivedi, Pravin K.; Nair, Aathira; Mehare, Rupali S.; Chaturvedi, Vikash; Joshi, Kavita; Shelke, V, Manjusha (Nanoscale Advances, 2020)
Conversion-type anode materials have been intensely studied for application in Li-ion batteries (LIBs) due to their potentially higher capacities than current graphite-based anodes. This work reports the development of a high-capacity and stable anode from a nanocomposite of N and S co-doped carbon spheres (NSCSs) with Co3O4 (NSCS-Co3O4). A hydrothermal reaction of saccharose withl-cysteine was carried out, followed by its carbonization. CSs when used as supports for conversion-type materials provide efficient electron/ion transfer channels, enhancing the overall electrochemical performance of the electrodes. Additionally, the heteroatoms doped in a carbon matrix alter the electronic properties, often increasing the reactivity of the carbon surface, and they are reported to be effective for anchoring metal oxide nanoparticles. Consequently, the NSCS-Co3O4 nanocomposites developed in this work exhibit enhanced and stable reversible specific capacity over several cycles. Stable cycling behavior was observed at 1 A g(-1)with 1285 mA h g(-1) of specific capacity retained after 350 cycles along with more than 99% of coulombic efficiency. This material shows excellent rate capability with a specific capacity of 745 mA h g(-1) retained even at a high current density of 5 A g(-1). Detailed DFT-based calculations revealed the role of doped supports in controlling the volume expansion upon lithiation.

Highly durable Li-ion battery anode from Fe3O4 nanoparticles embedded in nitrogen-doped porous carbon with improved rate capabilities - Deshmukh, Ashvini B.; Dwivedi, Pravin K.; Nalawade, Archana C.; Qureshi, Mohammed S.; Shelke, Manjusha V. (Journal of Materials Science, 2020)
For next generation, lithium-ion batteries (LIBs) developing high capacity anode materials are crucial with increasing demand of large-scale application. Conversion-type anode materials are promising if stable cycling behavior could be achieved. In this work, a nitrogen-doped porous carbon-Fe3O4(NPC-Fe3O4) nanocomposite is synthesized via a simple and scalable approach. Composite is prepared by pyrolysis of polymer silica hybrid PolyHIPE (high internal phase emulsion) into NPC, and Fe3O4 nanoparticles (NPs) are anchored on its surface via hydrothermal synthesis. As-prepared NPC-Fe3O4 nanocomposite delivers high reversible capacity of around 1001 mAhg(-1)at 0.1 Ag-1 current density and rate capabilities and displays excellent cycling stability as high as 95% capacity retention even after 400 cycles. Superior electrochemical performance of NPC-Fe3O4 is attributed to the hierarchical porous structure and nitrogen doping of carbon which shorten the diffusion path of Li+ and provide ample space to prevent aggregation of Fe3O nanoparticles. [GRAPHICS] .

High efficiency lithium storage in 3D composite foam of Co3O4 nanoparticles integrated carbon nanohorns - Dwivedi, Pravin K.; Parte, Golu; Thripuranthaka, M.; Shelke, Manjusha V. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2021)
A well-designed 3 dimensional (3D) nanocomposite foam of Co3O4 nanoparticles and functionalized carbon nano horns (CNH) is prepared by feasible wet chemistry followed by lyophilization. This 3D nanocomposite foam is evaluated electrochemically as anode material for lithium-ion battery (LIB). 3D hierarchical mesoporous hybrid of functionalized carbon nano horn-Co3O4 (CCO) shows excellent lithium storage properties with long cycle life due to high surface area, good conductivity, 3D interconnected mesoporous structure, mechanical and chemical stability and shortened diffusion path length for Li+ ions during lithiation-delithiation. The Co3O4 nanoparticles incorporated into interconnected CNH foam effectively increases the number of active sites of CCO nanocomposite and consequently increase in the reversible specific capacity and coulombic efficiency. Different compositions of CNH foam with Co3O4 nanoparticles are prepared, among which the CCO 1:1 foam displays reversible capacity of 797 mAhg1 at current density of 0.1 Ag-1 along with excellent rate performance. High specific capacity of around 702 mAhg(-1) is obtained even at the current density of 5 Ag-1.
Keywords: 3D CCO foam; carbon nanohorns; Excellent rate capability; Li ion diffusion coefficient; Long Cycle life

Evaluation of Fe3O4 incorporated functionalized carbon nanotube self-standing buckypaper as electrodes for solid-state symmetric supercapacitor - Bhaviripudi, Vijayabhaskara Rao; Dwivedi, Pravin K.; Pabba, Durga Prasad; Aepuru, Radhamanohar; Nakate, Umesh T.; Espinoza-Gonzalez, Rodrigo; Shelke, V, Manjusha (Journal of Energy Storage, 2023)
Iron (II, III) oxide and carbonaceous materials drawn considerable attention in energy storage owing to their special features. In this study, simple reverse co-precipitation, acid functionalization and vacuum filtration methods adopted to synthesis Fe3O4 nanoparticles of size 11 nm and -COOH acid functionalized multi-wall carbon nanotubes (FMWCNT). And further used them to prepare and optimize Fe3O4 in FMWCNT as 15 wt% and 25 wt% self-standing buckypapers of around 30-mu m thickness as electrodes for solid-state symmetric capacitor in the form of coin cell. The results show that 15 wt% and 25 wt% of Fe3O4-FMWCNT buckypapers hybrid nanostructures have Fe3O4 nanoparticles successfully incorporated in FMWCNT. The 25 wt% Fe3O4-FMWCNT electrodes with charge transfer resistance of 140 Ohm showed high areal specific capacitance (Cs) 78.5 mF/cm2 and retained 80 % of its Cs until 800 cycles even at high current density of 1 mA/cm2, scan rate of 100 mV/s whereas 15 wt% Fe3O4-FMWCNT showed low Cs of 47 mF/cm2 and retained 80 % of its Cs over 5000 cycles whereas only FMWCNT show Cs is 36 mF/cm2 with 54 Ohm. Finally, a solid-state symmetric supercapacitor coin cell with self-standing 25 wt% Fe3O4-FMWCNT buckypaper showed an excellent power density of 129.5 mW cm-3 and energy density of 3.6 mWh cm-3 is the innovation of the current work. This is mainly attributed to the combined effect of pseudocapacitive behavior from Fe3O4 by faradaic reaction with additional charge transfer resistance and electric double layer (EDLC) behavior from FMWCNTs by non-faradaic of electronic, ionic transport during charging-discharging. As-made solid-state symmetric supercapacitor appears as a high-performance storage device without extra support of current collectors for practical applications and for fabri-cation of planar capacitors.
Keywords: Buckypaper; Power density; specific capacitance; Symmetric supercapacitor